DESIGNING AN INTEGRATED COMPUTER PROGRAM FOR VEGETABLE PRODUCTION IN THE KINGDOM OF SAUDI ARABIA - R.A Bayoumi; Atta H.M.; El-Sehrawey M.H.; Selim Sh.M.; El-Hemiany A.; Abdullah Alsadon; Abdulrahman Alazba; Ibrahim Alshahwan; Abdulrahman Aldawood; Safwat Khalil (Arab Universities Journal of Agricultural Sciences, 2010)
Vegetable production provide great value in the agricultural production sector in the Kingdom of Saudi Arabia. Growers and agricultural engineers need a comprehensive database in Arabic lan-guage that can be available for use any time any where. Therefore, this research project was initiat-ed. The computer program was developed using Visual Basic Net 2005 which is one of the ad-vanced visual programming languages. We took into consideration easy usage and coherence be-tween all program components. Main results in-clude computer program with the data base, which includes: vegetable crops, diseases, insect pests and other pests that attacks vegetable crops, management tactics, cultural practices, irrigation requirements, planting dates, data search. Fur-thermore, field trips have been carried out to some vegetable farms in all the Kingdom regions. A digit-ized map of the Kingdom has been added to the program in addition to crop water and heat re-quirements. Various search capabilities have been developed in the program. After the completion of the program build up, verification trips have been carried out for five regions in the presence of farm-ers and extension specialists of the different direc-torate of the Ministry of Agriculture to test the accu-racy of steps used in the program. A manual for the computer program as well as leaflet on pro-gram set up and usage have been included. It is recommended to make this program available at the internet and distribute copies to the Ministry of Agriculture and its directorates as well as farmers.